Study of the mineralization potential of the intrusives around Valis (Tarom-Iran) (2014)
The study area is located in northwestern Iran in the central Iran zone, specifically the western Alborz sub-zone south of the Tarom-Hashtjin metallogenic zone. The exposed rock units in this area generally include Eocene volcanic rocks (lava flows and pyroclasts belonging to the Karaj formation) and Oligocene granitoid intrusive bodies. The intrusive bodies in the area have a petrographic composition of granite, syenite and monzonite and are mostly metaluminous. The dual characteristics of these intrusives (for example, the behavior of elements such as Rb, P, Ga/Al, Y/Nb, K/Na, and FeO/Fe2O3, the Rb/Nb ratios, the A/CNK molar ratios and the ACF and A/CNK-Fe2O3+FeO diagrams), some of which are consistent with the I nature and others with the S and A natures, show that the rocks are among hybrid granitoids and, in terms of the tectonic setting, lie within the WPG range. According to the Rb/Sr, Zr/Hf, K/Rb ratios, the granite melts that form the aforementioned bodies are not extremely evolved and have not undergone post magmatic activity, which would lead to mineralization. The Sm/Eu and Rb/Ba ratios and the behavior of Rb, Ba and Sr within the aforementioned granitoids show that the rocks are similar to average granitoids unrelated to Li, Be, Sn, W and Ta deposits; they fall within the range of barren granitoids but are partially fertile in Cu. ResumenEl área de este estudio está localizada en el noroeste de la zona central de Irán, específicamente en el oeste de la subzona de Alborz y al sur de la zona metalogénica de Tarom-Hashtjin. Las unidades de roca expuesta en esta área se clasifican generalmente como rocas volcánicas del Eoceno (flujos de lava y piroclastos pertenecientes a la formación Karaj) y como cuerpos granitoides intrusivos del Oligoceno. Los cuerpos intrusivos en el  área tienen una composición petrográfica de granito, sienita y monzonita mayormente metaluminosa. Las  características duales de estas intrusiones (por ejemplo, el comportamiento de de elementos como Rb, P, Ga/ Al, Y/Nb, K/Na, y Feo/Fe2O3, los índice de Rb/Nb, la proporción molar de los A/CNK y los diagramas ACF y A/CNK-Fe2O3+FeO), algunas de las cuales son consistentes con la índole I y otras con las índoles S y A, muestran que las rocas son granitoides híbridos y, en términos de orden tectónico, subyacen en la cadena WPG. De acuerdo con los índices Rb/Sr, Zr/Hf, K/Rb, los granitos fundieron la forma de los cuerpos sin desarrollarse completamente y sin registrar actividad magmática posterior, lo que llevó a la mineralización. Los índices Sm/Eu y Rb/Ba y el comportamiento del Rb, Ba y Sr al interior de los granitoides mencionados muestran que las rocas son similares al promedio de los granitoides no relacionados con los depósitos de Li, Be, Sn, W y Ta; estos incluyen en el rango de granitoides estériles, pero son parcialemente fértiles en Cu.